Numerical Analysis of Hydrodynamics for Bionic Oscillating Hydrofoil Based on Panel Method - Gang Xue; Yanjun Liu; Muqun Zhang; Hongpeng Ding (Applied Bionics and Biomechanics)
The kinematics model based on the Slender-Body theory is proposed from the bionic movement of real fish. The Panel method is applied to the hydrodynamic performance analysis innovatively, with the Gauss-Seidel method to solve the Navier-Stokes equations additionally, to evaluate the flexible deformation of fish in swimming accurately when satisfying the boundary conditions. A physical prototype to mimic the shape of tuna is developed with the revolutionized technology of rapid prototyping manufacturing. The hydrodynamic performance for rigid oscillating hydrofoil is analyzed with the proposed method, and it shows good coherence with the cases analyzed by the commercial software Fluent and the experimental data from robofish. Furthermore, the hydrodynamic performance of coupled hydrofoil, which consisted of flexible fish body and rigid caudal fin, is analyzed with the proposed method. It shows that the caudal fin has great influence on trailing vortex shedding and the phase angle is the key factor on hydrodynamic performance. It is verified that the shape of trailing vortex is similar to the image of the motion curve at the trailing edge as the assumption of linear vortex plane under the condition of small downwash velocity. The numerical analysis of hydrodynamics for bionic movement based on the Panel method has certain value to reveal the fish swimming mechanism.